Attitudes toward schooling in Vukovar: Implications for social reconstruction - Čorkalo Biruški, Dinka (2003)
The experiences of post-conflict societies show that the process of trust building and normalization of social life is far slower and more demanding than the material renewal. This process is especially difficult in divided communities, as Vukovar is, where Croats and Serbs live in the same town but with almost no mutual contacts. This division is evident in all aspects of social life, expanding also into the area of schooling. The children attend separate classes, divided according to the ethnicity, and the curriculum is provided either in Croatian or in Serbian language. In this way the basic condition for normalization of the inter-group relations &#8211 ; contact &#8211 ; is discouraged. Following the city community for more than three years (Ajduković and Čorkalo, 2002 ; 2003) we have heard from the parents of both ethnic backgrounds their worries and discontent with children separation in schools. The present study explores in more depth the attitudes of pupils, their parents and teachers toward separated vs. integrated schooling and toward the variety of aspects relevant for the social reconstruction of the community in the aftermath of war. The questionnaire was administered that encompassed several aspects of attitudes toward schooling: value of education for one&#8217 ; s life, attitudes toward school integration and social integration of children from different ethnic background in general, attitudes toward religious education in the schools, and attitudes toward multiculturalism. The results are discussed having in mind the complexity of the issues of minority education, possibilities of building cooperative inter-group relations and for social reconstruction of the divided community.